Fiber laser sensor for simultaneously axial strain and transverse load detection. (February 2015) - Yu, Kuanglu; Wu, Chongqing; Sun, Mingxuan; Lu, Chao; Tam, Hwa-Yaw; Zhao, Yao; Shao, Liyang
Highlights: A fiber sensor for simultaneous measurements of axial strain and transverse load is proposed and demonstrated. The sensor's characteristics are experimentally measured and discussed. Temperature and pump power's impacts on the measurement error are talked about, possible solutions are then given. Abstract: We demonstrate a distributed Bragg reflector (DBR) fiber laser sensor for simultaneous measurements of axial strain and transverse load, this sensor might be applied in structure health monitoring. In this scheme, transverse load introduces an additional birefringence and consequently a linear beat note frequency change of the orthogonally polarized lasing modes, while the axial strain can be simply deduced from the wavelength shift of the laser. The sensor's sensitivity is measured to be 1.33 kHz/mg and 1.266 pm/με for lateral load and axial strain respectively.